THE LEGAL FORCE OF IMPLEMENTING SEMA NUMBER 2 OF 2023 REGARDING INTERFAITH MARRIAGES BASED ON THE PERSPECTIVE OF LEGAL CERTAINTY - Pulungan, Muhammad Al Faisal; Pujiyono, Pujiyono; Saptanti, Noor (JURNAL DARMA AGUNG, 2024)
In general, everyone wishes to marry someone of the same faith so they can build and nurture a family with the same religion. However, in reality, interfaith marriages often occur in society due to unlimited human interactions and socialization, especially because Indonesia is a diverse country with many religious followers. The fact is, all religions in Indonesia prohibit interfaith marriages. In Law Number 1 of 1974 concerning marriage, Article 2 paragraph (1) states that "marriage is legitimate if carried out according to the laws of each respective religion and belief." This implies that a legitimate marriage must be conducted according to the same religion and belief, not different ones. However, there are still instances where some district courts grant applications for interfaith marriages. In Constitutional Court Decision Number 68/PUU/XII/2014, the Constitutional Court firmly rejected interfaith marriages, and the Supreme Court also issued SEMA Number 2 of 2023 regarding Guidelines for judges in adjudicating cases of applications for registration of marriages between people of different religions. Despite the clear prohibition, interfaith marriages continue to occur.